Negative Correlation between Serum Cytokine Levels and Cognitive Abilities in Children with Autism Spectrum Disorder - Sasayama, Daimei (J Intell, 2017)
Evidence suggests that cytokines may be one of the major factors influencing cognitive development in those with autism spectrum disorder (ASD). To shed light on the neural and cognitive mechanisms of ASD, we investigated the association between peripheral cytokine levels and cognitive profiles in children with ASD. The serum levels of 10 cytokines (granulocyte macrophage colony-stimulating factor, interferon (IFN)-γ, interleukin (IL)-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, and tumor necrosis factor-α) were examined in 14 children with ASD using the Human Ultrasensitive Cytokine Magnetic 10-Plex Panel for the Luminex platform. The Wechsler Intelligence Scale for Children (WISC) was administered to each subject, and the relationships between WISC scores and serum levels of the cytokines were examined. The full-scale intelligence quotient (IQ) was significantly negatively correlated with the levels of IL-6 (Spearman’s rank, p < 0.0001, false discovery rate q < 0.01). The levels of IL-6 and IFN-γ showed significant negative correlations with the verbal comprehension index (p < 0.001, q < 0.01) and working memory index (p < 0.01, q < 0.05), respectively. No other cytokines were significantly correlated with full-scale IQ or with any of the subscale scores of the WISC. The present results suggest negative correlations of IL-6 and IFN-γ levels with cognitive development of children with ASD. Our preliminary findings add to the evidence that cytokines may play a role in the neural development in ASD.